NEUROPROTECTIVE ROLES OF BDNF AND NGF IN ARSENIC-INDUCED NEUROTOXICITY: MECHANISMS AND THERAPEUTIC IMPLICATIONS - CHAURASIA, AYUSH; ANSARI, ZEESHAN; HEMA, G.; SINGH, ANJU; GUPTA, AJAY KUMAR (International Journal of Applied Pharmaceutics, 2025)
Arsenic-induced neurotoxicity is increasingly recognized as a major global health issue, leading to both developmental and degenerative neurological impairments, therefore, arsenic is becoming one of the potent environmental neurotoxins that can lead to significant health risks, particularly through long-term exposure via water, food, and air. Arsenic exposure can initiate a range of pathological events such as-disruption of mitochondrial function, oxidative stress, apoptosis, and inflammatory processes, which result in neuronal damage and cognitive dysfunction. Conversely, neurotrophins growth factors that regulate neuronal survival, growth, and function, are emerging as promising neuroprotective agents against such neurotoxic effects. This article explores the neuroprotective roles of BDNF (Brain-derived neurotrophic factor) and NGF (Nerve growth factor) in counteracting arsenic-induced neurodegeneration, through the analysis of epidemiology and mechanism-based preclinical studies of last decade. Arsenic disrupts neurotrophin signaling by inhibiting Trk (Tropomyosin receptor kinase) receptor phosphorylation and downstream survival pathways PI3K-AKT (Phosphoinositide 3-kinase–Protein kinase B), ERK-CREB (Extracellular signal-regulated kinase-cAMP response element-binding protein), thus contributing to neurodegeneration. In animal models, BDNF supplementation exhibited reduction in oxidative stress by 45–60%, neuronal apoptosis declined by about 55%, and improvement in cognitive function up to 40%. Additionally, NGF supplementation shows a 40-55% reduction in apoptosis. By integrating toxicological mechanisms with therapeutic perspectives, this narrative review underscores the potential of neurotrophin-based strategies to mitigate arsenic-related neurodegeneration and highlights future research directions for translational applications.